Effects of different microwave drying conditions on drying characteristics and quality of preserved apricots - ZHAO Hong-xia; WANG Ying-qiang; MA Yu-he; LIU Ye-rong; WEN Jian-hua; ZHANG Bian-fei (Shipin yu jixie)
Objective: This study aimed to improve the drying efficiency and product quality of preserved apricot. Methods: The preserved apricots were dried using the rotary microwave oven (RMD) and the microwave coupled with convection dryer (MCD). The effect of microwave power, microwave emission mode, cutting and material movement on drying characteristics, the scorching rate, color and sensory quality were investigated and compared with traditional hot air drying (HD). Results: Compared with 1 040 min (16 pieces) and 840 min (48 pieces) of HD, the drying time was significantly shortened by microwave drying, ranging from 40 to 400 min. The drying time could be shorten by large pulse ratio, high power or large material size, and the longest drying time was in MCD temperature controlled microwave. Both RMD and MCD static drying caused serious charring phenomenon in apricots, with the char rate ranging from 17% to 100%, which was higher than that in static drying. However, the char phenomenon was avoided in MCD static drying, and the color value and sensory evaluation of apricots in MCD static drying were closest to HD. The rehydration ratio was only 3.45%~5.17% different from HD, and the highest sensory evaluation score (87.2 points) was obtained. Conclusion: MCD temperature-controlled static drying can be used as an efficient method for apricots.